Sustainability Balanced Scorecard Approach to Internet of Things Enabled Logistics Systems. Issue 3 (3rd July 2022) - Keivanpour, Samira
Abstract: Performance evaluation is an essential part of assessing the sustainability of the logistics systems and the implications of Industry 4.0 technologies. This research proposes an integrated sustainability evaluation framework for logistics providers using a fuzzy-based simulation model. A sustainability balanced scorecard approach is used in a hierarchical model based on multiple Mamdani Fuzzy Inference Systems (FIS). The sustainability of Internet of Things (IoT) adoption for a logistics provider was demonstrated using a hypothetical case study. A Design of Experiment approach is applied to evaluate the validity of the model. Moreover, different defuzzification methods are used to test the robustness of the fuzzy inference systems. The proposed method can aid operational managers in assessing the contribution of IoT to the sustainability of logistics systems considering inventory, warehouse, and order fulfillment aspects.